Merit overrules theory of mind when young children share resources with others. - James Stack; Carlos Romero-Rivas (PLoS ONE)
Non-windfall approaches to sharing demonstrate pre-schoolers' sensitivity to merit-based distributions of resources. However, such studies have not considered (1) whether epistemic aspects of task performance, such as the relative accuracy of a co-worker, influences pre-schoolers' rates of sharing; and (2) how children's emerging social understanding may impact resource allocations in high- and low-merit situations. These issues are of theoretical importance as they may provide new information about the scope of pre-schooler's merit-based sharing behaviours. Moreover, as social understanding has been related to both increases and decreases in pre-schoolers' levels of sharing, providing a merit-based assessment of this relationship would allow for a concurrent assessment of recent conflicting findings. In this study, three- and four-year-olds (N = 131) participated in an unexpected transfer task which was followed by a resource generation picture card naming task with a reliable or unreliable (high- or low-merit) co-worker (a hand puppet). The results showed that children engage in more generous rates of sharing with a high-merit co-worker. This suggests that merit-based sharing is apparent in young children and extends to epistemic aspects of task performance. However, such sharing was constrained by a self-serving bias. Finally, we were not able to detect an effect of children's performance on the false belief task on sharing behaviours in the high- or low-merit trials, suggesting that these behaviours may not be modulated by social understanding during early childhood.